In vivo cardiac power generation enabled by an integrated helical piezoelectric pacemaker lead. (December 2019) - Dong, Lin; Closson, Andrew B.; Oglesby, Meagan; Escobedo, Danny; Han, Xiaomin; Nie, Yuan; Huang, Shicheng; Feldman, Marc D.; Chen, Zi; Zhang, John X.J.
Abstract: Long-term energy supply for electronic systems is challenging for implantable biomedical devices, like cardiac pacemakers. Energy harvesting can significantly extend the lifetime of these devices, however, no clinical translational technologies can efficiently convert the mechanical energy of the heart into electrical power without a thoracotomy and interfering with the cardiovascular functions. Almost all reported implantable cardiac energy harvesting designs sutured devices directly onto the epicardium or pericardium with potential risks to the patients. Here, we report a cardiac energy harvesting strategy, which is integrated into part of the existing pacemaker lead and otherwise with no direct contact of heart, by utilizing porous piezoelectric thin films in a bioinspired self-wrapping helical configuration for flexible integration with existing implantable medical devices. We demonstrate that this compact design can be seamlessly coupled with current leads without introducing additional implantation surgeries. In vivo studies under various conditions (anchoring, pacing, and calcium chloride infusion) are presented that demonstrate clinical translation in a porcine model. Both theoretical studies and in vitro experiments are also presented to validate the energy harvesting process. The scalability of the design is discussed, and the reported results demonstrate a 10 × 10 array of helical EH devices wrapping all through the lead (a mixed pattern of in series and parallel connections) would extend the lifetime of the pacemaker battery by 1.5 years. This innovative cardiac energy harvesting strategy represents a significant step forward for clinical translation without a thoracotomy for patients, suggesting a paradigm for biomedical energy harvesting in vivo . Graphical abstract: Image 1 Highlights: Low profile thin film cardiac energy harvesting strategy with no direct contact of heart. Bioinspired self-wrapping helical configuration for flexible integration with medical devices. In vivo studies demonstrate clinical translation in a porcine model. The device converts the complex vibrational, and bending/twisting motions of a pacemaker lead. An energy harvesting device yields an electrical output of 0.65 V in vivo .